(untitled) (Journal of Asian Development Studies, 2024)
This study, titled The Language of War and Peace: A Critical Discourse Analysis of Conflict in The Lord of the Rings, delves into the intricate ways in which J.R.R. Tolkien’s epic narrative constructs and represents concepts of war and peace. Utilizing Norman Fairclough’s Critical Discourse Analysis (CDA) framework (1941), this research investigates the novel’s linguistic and ideological dimensions of conflict. By examining key passages that depict significant moments of war, such as the Battle of Helm’s Deep and the Siege of Gondor, alongside moments of peace, including the Council of Elrond and Aragorn’s ascension to the throne, the study reveals how Tolkien’s language reflects and critiques power structures and moral values. The analysis highlights how Tolkien’s use of martial and peace-oriented language, including lexical choices and metaphorical structures, contributes to portraying heroism, resistance, and moral duty. It also uncovers the binary oppositions between good and evil underpinning the narrative, offering insights into how these elements reinforce and challenge traditional ideologies of conflict. The study demonstrates that Tolkien’s narrative glorifies heroism, provides a nuanced critique of violence, and advocates for unity and ethical leadership. By applying CDA to Tolkien’s work, this research contributes to a deeper understanding of the ideological implications of his portrayal of war and peace, providing valuable perspectives for literary scholars and critics. The study also opens avenues for future research, including comparative analyses with other fantasy literature and contemporary conflicts, to further explore how language influences perceptions of conflict and resolution